2022
DOI: 10.1001/amajethics.2022.319
|View full text |Cite
|
Sign up to set email alerts
|

How Should Representation of Subjects With LEP Become More Equitable in Clinical Trials?

Abstract: Underrepresentation of individuals with limited English proficiency (LEP) who speak Spanish is ongoing in phase 3 biomedical clinical trials and exacerbates health inequity. This article suggests strategies for increasing representation of Spanish speakers in clinical rials by emphasizing the importance of early engagement with Spanish language communities, inclusive participant recruitment, and collaborative trial design and implementation. Although investigators and institutions administering government-fund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…Additionally, COVID-19 treatment trials were typically conducted among inpatient populations, which were likely disproportionately Hispanic or Latino owing to the relative lack of primary care services on contracting COVID-19 and the increased risk of COVID-19–associated hospitalization among Hispanic or Latino groups . The present findings about Hispanic or Latino representation stand in contrast to prior studies for COVID-19 and other diseases, which have found low enrollment of Hispanic or Latino populations in trials owing to institutional and/or systemic racism, distrust of the health care system, lack of access to clinical trial centers, low socioeconomic status, and language and communication barriers . The underrepresentation of Hispanic or Latino participants indicated in some previous studies may also be related to poor reporting of Hispanic or Latino identity when using administrative records .…”
Section: Discussioncontrasting
confidence: 90%
“…Additionally, COVID-19 treatment trials were typically conducted among inpatient populations, which were likely disproportionately Hispanic or Latino owing to the relative lack of primary care services on contracting COVID-19 and the increased risk of COVID-19–associated hospitalization among Hispanic or Latino groups . The present findings about Hispanic or Latino representation stand in contrast to prior studies for COVID-19 and other diseases, which have found low enrollment of Hispanic or Latino populations in trials owing to institutional and/or systemic racism, distrust of the health care system, lack of access to clinical trial centers, low socioeconomic status, and language and communication barriers . The underrepresentation of Hispanic or Latino participants indicated in some previous studies may also be related to poor reporting of Hispanic or Latino identity when using administrative records .…”
Section: Discussioncontrasting
confidence: 90%
“…28 Given federal guidance on inclusion of non-English-speaking participants in clinical trials is even sparser, 14 it has become clear that measures are not routinely being taken to include participants with limited English proficiency in clinical trials. 9 By including individuals who speak different languages in clinical research, we include individuals of different identities and ancestries. Yet, language presents a unique consideration among other identities.…”
Section: Call For Systemic Changementioning
confidence: 99%
“…Although we are committed to understanding the many barriers that make the enrollment of a diverse population a challenge, we focus in this article specifically on language. There has been a call to increase inclusion of individuals with limited English proficiency in all phase 3 clinical trials, 9 yet this remains an elusive goal even for Parkinson's trials specifically focused on fostering inclusion of underrepresented populations in Parkinson's research. 8 Speaking a language other than that in which the trial has been designed raises several complex and unique challenges that may not be fully appreciated by scientists in study design.…”
mentioning
confidence: 99%
“…The alacrity with which white (non-Hispanic and Hispanic), English-speaking caregivers responded to the study-compared to the near nonexistent representation from the Spanish-speaking community-reflects a disparity in clinical research participation noted across communities with limited English proficiency (Alhalel et al, 2022;Cavazzoni et al, 2020;Egleston et al, 2015) and more generally, the deeper limitations of suggested approaches to outreach to and share information with these diverse communities (NYU Langone Health Office of Science and Research, Clinical and Translational Science Institute, 2022) that are further affected by rare conditions.…”
Section: Introductionmentioning
confidence: 99%